Zinc supplementation decreases basophilic stippling in rats exposed to lead - Budi Santosa; Hertanto Wahyu Subagio; Lisyani Suratmo; Henna Rya Sunoko (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUND Lead acetate inhibits pyrimidine-5’-nucleotidase resulting in ribonucleic acid and ribosome accumulation in erythrocytes (RBC), visible as basophilic stippling (BS). Lead exposure disrupts RBC membrane, shortens the RBC life span and decreases hematocrit. Zinc supplementation increases lead-binding proteins (metallothioneins). The study objective was to determine whether zinc supplementation prior to lead exposure decreases BS and increases the hematocrit in rats. METHODS The study was a randomized post-test only control-group trial, using 28 rats allocated to one control and 3 intervention groups (Zinc I, Zinc II, Zinc III) receiving 0.2 mg, 0.4 mg, and 0.8 mg of zinc by oral gavage daily for 3 weeks. All groups were then exposed to lead at 0.5 g/kg BW/day by gavage for 10 weeks. On the last day of the 10 weeks BS was determined from Giemsastained blood smears and hematocrit by hematology analyzer. Between-group differences were tested with one-way ANOVA, followed by Bonferroni’s test. RESULTS Mean BS was significantly decreasing 7.93 ± 0.99% in controls, 6.91 ± 1.04%, 4.66 ± 0.79%, and 1.73 ± 0.88%, respectively, in intervention groups (p=0.000). Mean hematocrit was significantly increasing 26.16 ± 3.60% in controls, and 30.33 ± 6.12%, 36.83 ± 3.31%, and 40.00 ± 4.77%, respectively, in intervention groups (p=0.000). One-way Anova and Bonferroni’s test showed significant differences in BS and hematocrit between controls and intervention groups receiving zinc supplementation of 0.4 and 0.8 mg (p=0.000). CONCLUSION Zinc supplementation before lead exposure significantly decreases basophilic stippling and increases hematocrit level in rats exposed to lead